2012
DOI: 10.3389/fphys.2011.00118
|View full text |Cite
|
Sign up to set email alerts
|

Transient Mesenteric Ischemia Leads to Remodeling of Rat Mesenteric Resistance Arteries

Abstract: Mesenteric ischemia/reperfusion (I/R) is associated with high rates of morbidity and mortality. We studied the effect of mesenteric I/R on structural and mechanical properties of rat mesenteric resistance artery (MRA) that, once disrupted, might impact the outcome of this devastating clinical condition. Superior mesenteric artery from Wistar–Kyoto rats was occluded (90 min) and reperfused (24 h). The effect of tezosentan, a dual endothelin (ET)-receptor antagonist, was studied in ischemic (IO) and sham-operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The origin of the SMA was identified, dissected, and occluded for 90 minutes using a silicone loop (Surg‐I‐Loop; Scanlan, Saint Paul, MN) slung around the SMA origin from the aorta. The duration of SMA occlusion is similar to other studies 23‐25 . Occlusion of the SMA, which resulted in intestinal color change, was confirmed by the absence of pulsation in the mesentery at visual inspection and using a dissecting microscope.…”
Section: Methodssupporting
confidence: 86%
“…The origin of the SMA was identified, dissected, and occluded for 90 minutes using a silicone loop (Surg‐I‐Loop; Scanlan, Saint Paul, MN) slung around the SMA origin from the aorta. The duration of SMA occlusion is similar to other studies 23‐25 . Occlusion of the SMA, which resulted in intestinal color change, was confirmed by the absence of pulsation in the mesentery at visual inspection and using a dissecting microscope.…”
Section: Methodssupporting
confidence: 86%
“…The intensity of total vascular fluorescence of anti-GPER and its colocalization with anti-VWF (merge between 488 and 555 filters) was measured in two rings of each animal, normalized by the analyzed area. Results were expressed as arbitrary units ( Caracuel et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Messenger RNA (mRNA) expression of 1) the nitric oxide synthase isoforms (eNOS, iNOS and nNOS), 2) the subunits of NAD(P)H-oxidase (Nox-1, p22 phox and p47 phox ) and 3) the superoxide dismutase (SOD) isoforms [cytoplasmic Cu, Zn (SOD1), mitochondrial Mn (SOD2) and extracellular Cu, Zn (SOD3)] were quantified by Syber green-based quantitative real-time PCR as previously described (Caracuel et al 2011;Márquez-Martín et al 2012). Primer sequences for rodent genes used in this study are shown in Table 2.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…Frozen sections (14 μm) were incubated with primary antibodies as follows: mouse monoclonal anti-eNOS (1:100; BD Biosciences, Franklin Lakes, NJ, USA) or a rabbit polyclonal anti-iNOS (1:50; Thermo Scientific, Rockford, IL, USA), anti-nNOS (1:100; Life Technologies Ltd, Paisley, UK) and anti-nitrotyrosine (1:100; Merck Millipore, Billerica, MA, USA). Sections were processed for immunofluorescence staining essentially as previously described (Caracuel et al 2011;Jiménez-Altayó et al 2009;Martínez-Revelles et al 2012). Quantitative analysis of fluorescence was performed with MetaMorph Image Analysis software (Molecular Devices, Sunnyvale, CA, USA).…”
Section: Immunofluorescencementioning
confidence: 99%